ANALISA PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA PADA MATA KULIAH GELOMBANG & OPTIK DENGAN PENEKANAN KONSEP DASAR FISIKA - PARLINDUNGAN SITORUS; MULA SIGIRO; THEODORA SIMATUPANG (LP2MTBM MAKARIOZ, 2019)
This research was conducted with the aim to improve cognitive understanding of Universitas HKBP Nommensen students of physics education program in the fifth semester of 2018/2019 school year in Wave and Optical subject by implementing Learning Cycle 7E Model emphasizing on the basic concept of physics. This research was a classroom action research, conducted with three different cycles and teaching materials for each cycle. Each cycle is evaluated, reflected and improved in order to achieve the learning indicators. From the results of cycle I evaluation, the average cognitive value was 28.61; Cycle II was 29.79 and Cycle III was 70.83. Gain <g> of cycle I to cycle II was of 0.02 with the lowest criteria; gain <g> of cycle II to cycle III was 0.58 with the medium category and gain <g> of cycle I to cycle III was 0.59 with moderate criteria. From the results of the t-test of cycle I to cycle II, the difference obtained was 0.14 (showing no difference); cycle II to cycle III was 15.12 (showing difference) and cycle I to cycle III was 21.12 (showing difference) with t table of 1.70. The average level of students’ understanding for cycle I was 26.8; cycle II was 30.4; and cycle III was 60.7. All the result were obtained by making significant improvements in cycle III, including teaching the basic concepts of counting before the learning process in cycle III was conducted. The results of the data analysis and discussion show an improvement in the understanding of Universitas HKBP Nommensen students of physics education program by implementing Learning Cycle 7E Model emphasizing on the basic concept of physics. It was achieved as long as the learning process was modified according to students' abilities and the supporting learning media appropriate to the learning process were provided.